Barriers and facilitators to dental care among culturally and linguistically diverse carers: A mixed‐methods systematic review. Issue 2 (27th March 2022) - Marcus, Kanchan; Balasubramanian, Madhan; Short, Stephanie; Sohn, Woosung
Abstract: Objectives: Culturally and linguistically diverse (CALD) communities experience widespread inequalities in dental care utilization. While, several studies have reported factors contributing to such inequalities, a synthesis of evidence is lacking for CALD carers. This review examined the barriers and facilitators to dental care utilization among CALD carers. Methods: Medline, CINAHL, ProQuest, Scopus and Web of Science were searched for dental utilization and related factors, without geographic limitations. An integrated mixed‐method design was adopted, where both qualitative and quantitative findings were combined into a single synthesis. Critical appraisal was conducted using JBI tools, and a Universal Health Coverage (UHC) framework guided the synthesis approach. Reliability and researcher triangulation occurred throughout the conduct of this review. Results: A total of 20 papers were included: qualitative ( n  = 8), quantitative ( n  = 8) and mixed method ( n  = 4). Studies were from Australia, Canada, South Korea, Trinidad and Tobago, United Kingdom and the United States. Three studies insufficiently reported confounding variables and nine qualitative papers lacked philosophical perspectives. Affordability was the foremost barrier at the system level, followed by psychosocial negative provider experiences and language/communication issues at the provider level. Cultural, knowledge, attitudes and beliefs were individual‐family level factors. Utilizing a UHC framework, the barriers and facilitators were aggregated at three levels; financial‐system, provider and individual‐family levels and illustrated in the rainbow model of CALD oral health. Conclusion: The review strengthens evidence for multilayered, system‐related policies and culturally sensitive provision of services for reducing oral healthcare inequalities in CALD carers.